Control of human hemoglobin switching by LIN28B-mediated regulation of BCL11A translation - Basak, Anindita (Nat Genet, 2020)
Increased production of fetal hemoglobin (HbF) can ameliorate the severity of sickle cell disease and β-thalassemia(1). BCL11A represses the genes encoding HbF and regulates human hemoglobin switching through variation in its expression during development(2–7). However, the mechanisms underlying the developmental expression of BCL11A remain mysterious. Here we show that BCL11A is regulated at the level of mRNA translation during human hematopoietic development. Despite decreased BCL11A protein synthesis earlier in development, BCL11A mRNA continues to be associated with ribosomes. Through unbiased genomic and proteomic analyses, we demonstrate that the RNA-binding protein LIN28B, which is developmentally expressed in a reciprocal pattern to BCL11A, directly interacts with ribosomes and BCL11A mRNA. Furthermore, we show that BCL11A mRNA translation is suppressed by LIN28B through direct interactions, independent of its role in regulating let-7 microRNAs, and BCL11A is the major target of LIN28B-mediated HbF induction. Our results reveal a previously unappreciated mechanism underlying human hemoglobin switching that illuminates new therapeutic opportunities.